Disinhibition, a Circuit Mechanism for Associative Learning and Memory - Letzkus, Johannes J; Wolff, Steffen B E; Lüthi, Andreas (Neuron (Cambridge, Mass.), 2015)
Although a wealth of data have elucidated the structure and physiology of neuronal circuits, we still only have a very limited understanding of how behavioral learning is implemented at the network level. An emerging crucial player in this implementation is disinhibition--a transient break in the balance of excitation and inhibition. In contrast to the widely held view that the excitation/inhibition balance is highly stereotyped in cortical circuits, recent findings from behaving animals demonstrate that salient events often elicit disinhibition of projection neurons that favors excitation and thereby enhances their activity. Behavioral functions ranging from auditory fear learning, for which most data are available to date, to spatial navigation are causally linked to disinhibition in different compartments of projection neurons, in diverse cortical areas and at timescales ranging from milliseconds to days, suggesting that disinhibition is a conserved circuit mechanism contributing to learning and memory expression.